ASSESSMENT OF THE POTENTIAL ROLE OF L- METHIONINE ON NICKEL SULFATE INDUCED RENAL INJURY AND OXIDATIVE STRESS IN RAT - Bouhalit, Samira; Kechrid, Zine (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was designed to investigate the possible protective role of methionine (Met) in nickel sulfate induced oxidative stress in renal tissue. Methods: Rats were divided into the following groups: Healthy control; L-methionine (Met, 100 mg/kg, orally); nickel sulfate (Ni, 20 mg/kg, intraperitoneally); and combination Ni+Met. The experiment lasted 21 days. Antioxidant and renal function parameters with histological study were performed. Results: In the Ni group, marked renal damage was noticed with the significant elevation in the levels of creatinine, urea, and uric acid in serum. Animals also showed a significant rise in the lipid peroxidation level with a concomitant decrease in glutathione (GSH) and various antioxidant enzymes GSH peroxidase, catalase, and superoxide dismutase. Moreover, these changes in rats given the combined therapy nickel plus methionine were significantly less than those of group nickel, met prevented these alterations and maintained the antioxidant status. Histopathological examination of the kidney tissue proved the protective effect of Met against nickel toxicity. Conclusions: These results demonstrated that methionine augments antioxidant defense against nickel-induced toxicity and provides evidence that it has therapeutic potential as a renoprotective agent.